2013
DOI: 10.1111/rda.12163
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium aviumsubsp.paratuberculosisDetected in the Reproductive Tract of Cows from an Infected Herd

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP), the causal agent of paratuberculosis, was detected by quantitative real-time IS900 PCR in the follicular fluid from the reproductive tracts of cows originating from one infected herd. As well as being detected in follicular fluid of cows shedding bacteria in their faeces, MAP was also detected in the follicular fluid of one apparently healthy, non-shedding individual cow. The finding of MAP in follicular fluid is unexpected and could contribute to the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…), semen (Givens and Marley ) and, more recently, in follicular fluid and uterine flush (Pribylova et al. ). These sites indicate that MAP could affect the reproductive performance of the dairy cow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), semen (Givens and Marley ) and, more recently, in follicular fluid and uterine flush (Pribylova et al. ). These sites indicate that MAP could affect the reproductive performance of the dairy cow.…”
Section: Introductionmentioning
confidence: 99%
“…Because MAP is less prevalent in beef cows, the economic impact of this disease is higher in dairy cattle (Roussel 2011). An infected animal sheds bacteria mainly through the faeces and milk (Streeter et al 1995), although the bacterium has also been detected in muscular tissue (Mutharia et al 2010), mammary gland (Lambeth et al 2004;Hasonova et al 2009), testes, epididymis or seminal vesicles (Ayele et al 2004;Khol et al 2010), semen (Givens and Marley 2008) and, more recently, in follicular fluid and uterine flush (Pribylova et al 2013). These sites indicate that MAP could affect the reproductive performance of the dairy cow.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the venereal transmission of MAP by semen was never demonstrated in the past. As opposed to this, it is generally accepted that MAP is transmitted vertically from the cow to their foetus in utero (Pribylova et al., ). A meta‐analysis indicated that the total prevalence of calves infected in utero was 13% among infected cattle (Whittington and Windsor, ).…”
Section: Introductionmentioning
confidence: 99%